2013
DOI: 10.2131/jts.38.269
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin, a sensitive urinary biomarker of acute kidney injury in dogs receiving gentamicin

Abstract: -A sensitive urinary biomarker for acute kidney injury (AKI) was investigated in beagle dogs with nephrotoxicity induced by gentamicin. Gentamicin sulphate at 25 or 50 mg/kg was injected (s.c.) for 9 days, and conventional urinalysis, ELISA assay of neutrophil gelatinase-associated lipocal (NGAL) in urine, blood chemistry, and pathological examinations were performed. The dog given gentamicin at 25 mg/kg only showed slight deposition of lysosomal granules in the proximal tubular epithelium of the kidneys witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 19 publications
3
42
0
1
Order By: Relevance
“…Sustained increase in urinary NGAL was reported to be as long as 5 days post damage in humans. The increase in urinary NGAL is considered to be due to an increase in NGAL synthesis and failure of complete reabsorption of NGAL in the proximal tubular epithelia (Kai et al, 2013;Alge and Arthur, 2015). The results in the present study suggested that NGAL could be the most useful BM for the detection of earlier damages of the proximal and/or distal tubules among all urinary BMs and enzymes in cynomolgus monkey.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Sustained increase in urinary NGAL was reported to be as long as 5 days post damage in humans. The increase in urinary NGAL is considered to be due to an increase in NGAL synthesis and failure of complete reabsorption of NGAL in the proximal tubular epithelia (Kai et al, 2013;Alge and Arthur, 2015). The results in the present study suggested that NGAL could be the most useful BM for the detection of earlier damages of the proximal and/or distal tubules among all urinary BMs and enzymes in cynomolgus monkey.…”
Section: Discussionsupporting
confidence: 48%
“…The usefulness of NGAL to detect the damage of the renal tubules has been reported in rats (Han et al, 2012;Phillips et al, 2016) and dogs (Kai et al, 2013;Zhou et al, 2014). After renal ischemia or nephrotoxicity, intrarenal NAGL synthesis is dramatically upregulated at protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Urine immunoglobulin G (uIgG) and urine retinol binding protein (uRBP) were increased in dogs with primary CKD7 and those with renal dysfunction secondary to various systemic diseases including pyometra, babesiosis, and snake envenomation 7, 8, 9, 10, 11, 12, 13, 14, 15. Urine, plasma, and serum neutrophil gelatinase‐associated lipocalin (NGAL) and urine N‐acetyl‐β‐D‐glucosaminidase (uNAG), a renal tubular enzyme, are tubular markers increased in both acute and CKD in dogs 7, 11, 12, 15, 16, 17, 18, 19, 20, 21, 22. Neutrophil gelatinase‐associated lipocalin originates not only in the renal tubules but also from neutrophil granules and many other organs 23.…”
mentioning
confidence: 99%
“…Neutrophil gelatinase‐associated lipocalin originates not only in the renal tubules but also from neutrophil granules and many other organs 23. Novel urine biomarkers are not regularly used as diagnostic tools for evaluation of renal disease in veterinary medicine, and few veterinary studies correlate biomarkers with histologically proven renal damage7, 12, 13, 18 and case outcome 4…”
mentioning
confidence: 99%
“…The significant increase of NGAL in urine was detected as early as 12 h after surgery, much earlier than the increase in serum creatinine. Urinary NGAL was recommended as a sensitive and specific biomarker for the detection of AKI, for prediction of nephrotoxicity, and to screen patients at risk for AKI (Table 1) (Lee et al 2012;Kai et al 2013;Hsu et al 2014a;Zhou et al 2014). NGAL was found to be a more sensitive biomarker for the detection of gentamicin-induced renal proximal tubular toxicity than NAG (Zhou et al 2014).…”
Section: Neutrophil Gelatinase-associated Lipocalinmentioning
confidence: 99%